2013
DOI: 10.1111/odi.12173
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant profile of salivary glands in high fat diet‐induced insulin resistance rats

Abstract: Parotid and submandibular glands of rats react differently when exposed to insulin resistance condition; however, the parotid glands seem to be more affected. The main source of antioxidants is parotid glands of rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 19 publications
6
35
2
1
Order By: Relevance
“…After 8 weeks of the study we observed a 30% increase in body weight, a nearly 100% increase in insulin content, and a 70% increase in the concentration of glucose. We also noted that HFD led to IR, as confirmed by 200% increase in HOMA-IR, which is consistent with our results as well as those of other researchers [6,16,19,42,43].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…After 8 weeks of the study we observed a 30% increase in body weight, a nearly 100% increase in insulin content, and a 70% increase in the concentration of glucose. We also noted that HFD led to IR, as confirmed by 200% increase in HOMA-IR, which is consistent with our results as well as those of other researchers [6,16,19,42,43].…”
Section: Discussionsupporting
confidence: 93%
“…A negative correlation between the activity of caspase 3, concentration of mitochondrial proteins, and peroxidase activity may suggest that apoptotic death of submandibular gland cells is so severe that leads to impairment of their function, as observed earlier by de la Cal et al [50]. It is noteworthy that peroxidase is the only protein produced exclusively in salivary glands and is a determinant of their secretory function [19].…”
Section: Discussionmentioning
confidence: 76%
“…All variables were expressed as total value/specific activity (ratio of specific protein to total protein). A reason of such results presentation was explained in the previous studies .…”
Section: Methodsmentioning
confidence: 73%
“…In rats with insulin resistance, the parotid glands have been reported to react differently from the submandibular ones, because the former seemed to be more affected despite being the main sources of antioxidants. 37 Regarding the second point, genetic susceptibility may play a role in a subset of T2D patients, so that they would be prone to developing multiple oncocytic cysts. In keeping with this idea, the occurrence of diabetic nephropathy has been related to several GLUT1 single-nucleotide polymorphisms.…”
Section: Discussionmentioning
confidence: 99%